SPEAKING ABSENCE CLUES - Dr. Csaba Fenyvesi; Dr. Vanessza Fábián (Національний науковий центр «Інститут судових експертиз ім. Засл. проф. М.С. Бокаріуса», 2024)
This study emphasizes that absence clues can also convey important messages about the circumstances of the crime and the identity of the perpetrator.
Keywords: crime scene investigation; material remain; electronic data; absence clue